2018
DOI: 10.1007/s00384-018-3083-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of a tumorous involvement of the mesorectal fascia and locoregional lymph nodes in locally advanced rectal cancer using DCE-MRI

Abstract: DCE-MRI considerably increases both sensitivity and specificity for the detection of small mesorectal lymph node metastases (≥ 5 mm but < 10 mm) and sufficiently improves specificity of a suspected MRF infiltration in patients with locally advanced rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…36 T1+C sequences, which can be used to indicate tumor blood supply, can be better evaluate tumor invasiveness because the growth, development and metastasis of tumors depend on complex microvessels for nutrition. 37 Both T2WI and T1+C sequences showed high predictive value for treatment response in the present study, which is important for predicting the outcome of treatment. Secondly, our study differed from earlier studies limited to radiomics in that clinical data were also incorporated into the model as important factors.…”
Section: Discussionsupporting
confidence: 57%
“…36 T1+C sequences, which can be used to indicate tumor blood supply, can be better evaluate tumor invasiveness because the growth, development and metastasis of tumors depend on complex microvessels for nutrition. 37 Both T2WI and T1+C sequences showed high predictive value for treatment response in the present study, which is important for predicting the outcome of treatment. Secondly, our study differed from earlier studies limited to radiomics in that clinical data were also incorporated into the model as important factors.…”
Section: Discussionsupporting
confidence: 57%
“…Grovik et al showed that a low K trans of the primary tumor can predict the presence of nodal metastasis (63), which can be achieved by dynamic contrastenhanced MRI (DCE-MRI) (64,65). In addition to DCE-MRI, special diffusion-weighted MRI parameters are helpful in differentiating metastatic lymph nodes (45,66).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the studies are presented in Table 1. The reference standards were divided into the following five categories according to different morphological criteria: (A) a short-axis diameter of 5 mm (22-34), (B) morphological standard, including an irregular border and mixed-signal intensity within the lymph node (35)(36)(37)(38)(39)(40), (C) a short-axis diameter of 5 mm with the morphological standard (11,(41)(42)(43)(44)(45)(46)(47)(48), (D) a short-axis diameter of 8 mm with the morphological standard (49)(50)(51)(52), and (E) a short-axis diameter of 10 mm with the morphological standard (11,45,53,54). In all of the included articles, 36 indirectly evaluated the lymph node stage of patients through histopathology and 5 (9,41,42,55,56) identified the node-by-node correspondence between lymph node MRI scans and histopathologic results.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…18 Semi-quantitative maps for plasma flow and mean transit time were calculated by deconvolution of tissue concentrations with the arterial input function. 17,19…”
Section: Mri and Dce-mri Postprocessingmentioning
confidence: 99%